Prohibition of Ownership of Foreign Citizens' Land Through A Nominee Agreement Based on The Principle of Legal Certainty - Sulistiyani, Nia (Magister Kenotariatan Universitas Pasundan, 2024)
These issues highlight a significant gap in the regulatory framework concerning foreign residential ownership in Indonesia. The absence of clear guidelines against nominee practices and the lack of enforcement mechanisms for violations pose challenges to the legal certainty and integrity of land rights transactions. Additionally, the minimal role of community participation in these processes raises questions about the inclusivity and transparency of foreign land ownership provisions. Overall, the situation underscores the need for further regulatory improvements to address these shortcomings and ensure a more robust, fair, and transparent framework for foreign residential ownership in Indonesia. The research method used is a legal analysis, using a qualitative approach with secondary data. The research found that transferring ownership rights to land to foreigners violated the principle of nationality and the Indonesian Agrarian Law, resulting in the land being returned to the state without reimbursing foreigners and Indonesian citizens for the losses. Furthermore, the legal status of a nominee agreement regarding the ownership of land rights by foreigners must meet the requirements for the agreement's validity and principles to obtain legal status.